2018
DOI: 10.21037/jtd.2017.12.67
|View full text |Cite
|
Sign up to set email alerts
|

The management of chemical pleurodesis with viscum album in patients with persistent air leakage

Abstract: Air leaks remain an important cause of morbidity. This viscum album pleurodesis could be considered as an option for the treatment of prolonged air leak patients, associated with acceptable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Numerous drugs such as talc, iodopovidone, doxycycline, minocycline, bleomycin, autologous blood, and OK432 have been used to treat seromas or malignant pleural effusion. Although the most effective drug remains to be identified, V. album extract is a newly introduced chemical agent that has been extensively studied given its low risk of adverse reactions and good therapeutic effects [8]. One of the ingredients of V. album extract is viscumin, which is intensely toxic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous drugs such as talc, iodopovidone, doxycycline, minocycline, bleomycin, autologous blood, and OK432 have been used to treat seromas or malignant pleural effusion. Although the most effective drug remains to be identified, V. album extract is a newly introduced chemical agent that has been extensively studied given its low risk of adverse reactions and good therapeutic effects [8]. One of the ingredients of V. album extract is viscumin, which is intensely toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it aids in eliminating dead space through immune responses that stimulate the synthesis of macrophage colony-stimulating factors and increase the concentrations of interferon, interleukins, tumor necrosis factors, and natural killer cells [9]. Treatments using V. album extract have been reported to lead to mild adverse events such as local heat sensations and local pain, which tend to resolve shortly afterward [7,8]. In fact, one of our patients experienced a local heat following V. album extract injection, which had improved by the next day without systemic fever or other complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important issues in the treatment of PSP is preventing recurrence. Although surgery is the most effective treatment for PSP, the recurrence rate of pneumothorax remains 5-15% after thoracoscopic surgery [3][4][5][6]11,12 . In order to minimize recurrence rate of postoperative pneumothorax, chemical pleurodesis has been performed simultaneously with resection or sequentially.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interest has emerged in methods of whole-capsule sclerotherapy for use before considering surgical methods. In the field of thoracic surgery, Abnobaviscum is used to treat adhesions in cases of malignant pleural effusion, and an attempt has been made to use this product to treat seroma [6]. Some studies have reported Abnobaviscum to be effective against malignant pleural effusion, and its efficacy as a sclerosing agent has also been recognized [7][8][9].…”
Section: Introductionmentioning
confidence: 99%